The central position of education in knowledge mobilization: insights from network analyses of spatial reasoning research across disciplines - Woolcott, Geoff; Chamberlain, Dan; Hawes, Zachary; Drefs, Michelle; Bruce, Catherine D.; Davis, Brent; Francis, Krista; Hallowell, David; McGarvey, Lynn; Moss, Joan; Mulligan, Joanne; Okamoto, Yukari; et al. (Scientometrics, 2020)
Knowledge mobilization is becoming increasingly important for research collaborations, but few methodologies support increased knowledge sharing. This study provides insights, using a reflective narrative, into a transdisciplinary knowledge-sharing investigation of the connectivity of educational research to that of other disciplines. As an exemplar for educational research, the study evaluated the use of spatial search terms from mathematics education using: 1) an initial descriptive statistical analysis combined with bi modal network analysis of highly cited articles; and, 2) a second more comprehensive unimodal analysis using bibliographic coupling networks. This iterative analytical process provided a major if surprising insight—although Education is not particularly well connected bidirectionally to many subject areas, it appears to act as a distribution centre for knowledge mobilization, providing a central hub for gathering and analysing knowledge from across disciplines in order to generate the complex system of information that underpins society.